2020
DOI: 10.1155/2020/9585047
|View full text |Cite
|
Sign up to set email alerts
|

The Effects and Mechanism of Quercetin Dietary Supplementation in Streptozotocin-Induced Hyperglycemic Arbor Acre Broilers

Abstract: Quercetin, a flavonoid found in fruits and vegetables, is widely distributed as a secondary metabolite in the plant kingdom. Oxidative stress plays a role in the pathogenesis of diabetes mellitus (DM). The present study investigated the effects of quercetin dietary supplementation on streptozotocin- (STZ-) induced hyperglycemic Arbor Acre (AA) broilers by determining the levels of fasting blood glucose (FBG), fasting insulin (FINS), biochemical indicators, oxidative stress markers, inflammatory cytokines conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 67 publications
4
14
0
1
Order By: Relevance
“…In the current study, 0.2 g/kg quercetin supplementation significantly increased mRNA and protein expression of PI3K and protein expression of PKB ( P < 0.01, P < 0.05); 0.6 g/kg quercetin supplementation significantly increased protein expression of PI3K and PKB ( P < 0.01, P < 0.01) ( Figures 2 , 3 ). Taken together, in line with the previous research that quercetin improved lipid metabolism and reduced abdominal fat deposition by activating PI3K/PKB signal pathway ( Ying et al, 2020 ). And together with the results of AMPK in this experiment, our findings indicated that quercetin increased the expression of AMPK via stimulating PI3K-PKB/AKT kinase activity.…”
Section: Resultssupporting
confidence: 92%
“…In the current study, 0.2 g/kg quercetin supplementation significantly increased mRNA and protein expression of PI3K and protein expression of PKB ( P < 0.01, P < 0.05); 0.6 g/kg quercetin supplementation significantly increased protein expression of PI3K and PKB ( P < 0.01, P < 0.01) ( Figures 2 , 3 ). Taken together, in line with the previous research that quercetin improved lipid metabolism and reduced abdominal fat deposition by activating PI3K/PKB signal pathway ( Ying et al, 2020 ). And together with the results of AMPK in this experiment, our findings indicated that quercetin increased the expression of AMPK via stimulating PI3K-PKB/AKT kinase activity.…”
Section: Resultssupporting
confidence: 92%
“…Quercetin is used to prevent obesity-induced muscle inflammation and sarcopenia [ 119 ]. Ying et al [ 120 ] suggested that quercetin can decrease the levels of malondialdehyde (MDA) and NO by changing the activity of antioxidant enzymes, activating the expression of PI3K/PKB signalling pathway-related genes, regulates glucose metabolism, reduces oxidative damage, and has a protective effect on ascorbic acid therapy.…”
Section: Applications Of Quercetinmentioning
confidence: 99%
“…Quercetin could reduce lipid deposition in broiler chicks by promoting PPARα-regulated lipid decomposition [38], reducing the expression levels of SREBP1, PPARγ, and HMGR in the liver [39], and activating P13K/PKB, AMRK, and/or cAMP signal pathway [39][40][41]. It has been reported that quercetin supplementation reduced the increase of adipose tissue weight induced by feeding with a high-fat diet in rats [32,42,43].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%